PHILOSOPHICAL UNDERSTANDING OF THE NATURE OF VIOLENCE - N. M. Boychenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. In order to consistently distinguish between violence, which is always primarily a destructive force, and the civilized use of force that involves constructive, creative goals, one should explore the main possible philosophical approaches to understand the nature of violence and try to give it a systematic outline. Methodology. This study uses a systematic approach to identify the internal relationship between different forms of violence and, accordingly, the counteraction against violence. Also, the author uses an axiology to identify the values that are the basis for distinguishing violence from its prototypes, as well as for the distinction between violence and coercion, as well as different types of coercion. Originality. This article presents significant clarifications on the classification of types of violence, in particular, it is clearly established that certain types of violence can not have ethical relevance, since they belong to the sphere of biology (expansion, aggression) or social anthropology (cultural, institutional coercion). Actually violence or violence in the narrow sense implies the existence of will, consciousness and destructive purpose. Accordingly, counteraction against violence should include the formation of a certain non-violent type of will, non-violent culture and creative, constructive goals. This requires both personal effort and institutional support and the availability of appropriate moral traditions. Ethical theory is intended to clarify and systematize these efforts. In this sense, ethics is the core of practical philosophy. To the extent that the influence of ethics on changes in human culture and sociality in the counterfactual regime is increasing, one should also speak of the anthropological significance of ethics. Conclusions. From the socio-philosophical point of view, it is necessary to specify exactly which social institutions and in which constellation generate violence. The ethical aspect of the study of violence involves categorizing the problem in terms of good and evil: violence is evil, as opposed to coercion, which can be justified, legitimated - but always from the point of view of promoting the development of society and the individual, encouraging the disclosure of his creative potential. Counterfactuality acts as an important ethical category, which reveals the transformation mechanism applied by human relative to himself and society while focusing on the values of goodness and other constructive and creative values.